2019
DOI: 10.31698/ped.46032019006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del manejo avanzado de la vía aérea en un departamento de emergencia pediátrico

Abstract: Introducción: La intubación endotraqueal en pacientes críticamente enfermos es un procedimiento de riesgo que requiere alta competencia en el manejo de la vía aérea. Es esencial conocer las habilidades de los médicos de emergencia pediátrica en el manejo avanzado de vías aéreas y de vías aéreas difíciles. Objetivo: Describir el manejo avanzado de vías aéreas y vías aéreas difíciles en un departamento de emergencia pediátrico. Materiales y Métodos: Estudio observacional, descriptivo y prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding the profile of patients who are intubated in pediatric emergencies, this is data that varies greatly depending on the center studied [3][4][16][17][18][21][22][23] , and there are few recent studies with an adequate sample. In this review, the study carried out by Céspeez et al 19 identified that the main indication for intubation was cardiopulmonary failure, with this and respiratory failure also being associated with greater difficulty in carrying out the procedure. Furthermore, more than half of the intubated patients were less than 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the profile of patients who are intubated in pediatric emergencies, this is data that varies greatly depending on the center studied [3][4][16][17][18][21][22][23] , and there are few recent studies with an adequate sample. In this review, the study carried out by Céspeez et al 19 identified that the main indication for intubation was cardiopulmonary failure, with this and respiratory failure also being associated with greater difficulty in carrying out the procedure. Furthermore, more than half of the intubated patients were less than 1 year of age.…”
Section: Discussionmentioning
confidence: 99%